Kesadaran Tren Fast Fashion pada Remaja di Kota Bandung - Priscillia, Monica; Achdiani, Yani; Abdullah, Mirna Nur Aulia (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
The fast fashion trend is highly popular among the public, especially teenagers, because it offers a wide variety of clothing models that change quickly. However, behind this globally popular trend, there are many negative impacts. The purpose of this study is to raise awareness about the negative impacts of the fast fashion trend among teenagers in Bandung City, who are consumers of fast fashion products. This study uses a descriptive quantitative method through a questionnaire presented to 100 respondents, with the criteria being late-stage teenage girls aged 18-21 years. The results of this study indicate that most respondents are aware of the negative impacts caused by this trend and intend to switch to better fashion choices, such as using eco-friendly products or reducing the use of fast fashion products.